Green gains: a case for South African-listed firms - Gichanga, John Mwati (School of Economics, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) performance on firm value and profitability for firms listed on the South Africa Stock Exchange from 2013 to 2021, using data from Bloomberg. To mitigate possible endogeneity, we utilized the two-stage least squares (2SLS) regression model, using lagged ESG scores (L2), ESG- related bonuses, and executive compensation as instruments. Our findings reveal that strong ESG performance positively influences firm profitability, but negatively impacts firm value as measured by Tobin's Q. The study suggests that ESG can enhance a firm's efficiency in its current operations, but it does not significantly contribute to its value creation. Furthermore, the Governance dimension of ESG is not statistically significant in both Tobin's Q and ROA models. Fixed Effects Model (FEM) analysis yielded insignificant results, highlighting the potential effects of endogeneity and its consequences if not addressed. This research contributes to the literature on ESG and financial performance by demonstrating the effectiveness of using robust instrumental variables and controlling for unobserved time- varying factors to derive unbiased estimates. The insights gained from this study can inform policymakers, industry leaders, and academics about the strategic integration of ESG considerations into corporate and investment practices, ultimately fostering sustainable development and enhancing financial performance.